A proposal for Latin American historical centers from the integral perspective of the landscape - González-Biffis, Alejandra (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
The results of the doctoral thesis, presented in this study, propose a methodology to contribute to the assessment, intervention and management of Latin American Historical Centers (hereinafter CH) as Historic Urban Landscapes (PUH). The proposal arises from recognizing that, from the large number of interventions carried out in the HCs from the 70s and 80s to the present day, on a few occasions they have managed to respond to the problems that have motivated them, or to comprehensively address the complexity of CH. To arrive at the proposal, an explanatory, qualitative and quantitative research has been developed. In principle, the theoretical-conceptual framework has been elaborated; Subsequently, the problems of HCs and the various intervention and management strategies implemented have been studied in depth; and finally, a methodology has been developed that seeks to articulate the various dimensions of sustainable urban planning from the integral perspective of the Landscape.